The nightingale (St. Martin's Press, St. Martin's Publishing Group, Macmillan Audio, 2015)
"An epic love story and family drama set at the dawn of World War II"--Provided by publisher. "Viann and Isabelle have always been close despite their differences. Younger, bolder sister Isabelle lives in Paris while Viann lives a quiet and content life in the French countryside with her husband Antoine and their daughter. When World War II strikes and Antoine is sent off to fight, Viann and Isabelle's father sends Isabelle to help her older sister cope. As the war progresses, it's not only the sisters' relationship that is tested, but also their strength and their individual senses of right and wrong. With life as they know it changing in unbelievably horrific ways, Viann and Isabelle will find themselves facing frightening situations and responding in ways they never thought possible as bravery and resistance take different forms in each of their actions"--Provided by publisher.

House of Hollow (G. P. Putnam's Sons, Books on Tape, Penguin Young Readers Group, 2021)
"Iris and Vivi work to uncover their dark, dangerous, and possibly magical past when their older sister Grey goes missing"--

The identicals (Hachette Audio, Little, Brown and Company, 2017)
Nantucket is only two and a half hours away from Martha's Vineyard by ferry. But the two islands might as well be worlds apart for a set of identical twin sisters who have been at odds for years. ust because twins look exactly the same doesn't mean they're anything alike - and Tabitha and Harper Frost have spent their whole lives trying to prove this point. When a family crisis forces them to band together - or at least appear to - the twins come to realise that the special bond that they share is more important than the resentments that have driven them apart.

Island girls: a novel (Ballantine Books, Random House Publishing Group, Books on Tape, 2013)
NATIONAL BESTSELLER Nancy Thayer returns to her beloved Nantucket in a highly emotional, wholly entertaining tale of three sisters forced to confront the past over one event-filled summer on the island. Charming ladies’ man Rory Randall dies with one last trick up his sleeve: His will includes a calculating clause mandating a summer-long reunion for his daughters, all from different marriages—that is, if they hope to inherit his posh Nantucket house. Relations among the three sisters are sour thanks to long-festering jealousies, resentments, and misunderstandings. Arden, a successful television host in Boston, hasn’t been back to the island since her teenage years, when accusations of serious misbehavior led to her banishment. College professor Meg hopes to use her summer to finish a literary biography and avoid an amorous colleague. And secretive Jenny, an IT specialist, faces troubling questions about her identity while longing for her sisters’ acceptance.   To their surprise, the three young women find their newfound sisterhood easier to trust than the men who show up to complicate their lives. And if that weren’t problematic enough, their mothers descend on the island. When yet another visitor drops by the house with shocking news, the past comes screaming back with a vengeance. Having all the women from his life under his seaside roof—and overseeing the subsequent drama of that perfect storm—Rory Randall might just be enjoying a hearty laugh from above.   Nancy Thayer’s novel insightfully illustrates how the push and pull of family altercations make us whole. It’s how the Randall sisters come to forgive, and learn to open their hearts to love. Praise for Island Girls “Nancy Thayer is one of my favorite writers, and Island Girls is one of her best. The Randall sisters are like your own family members or your best friends: funny, smart and emotional, infuriating and good-hearted. Here is a book to be savored and passed on to the good women in your life.”—New York Times bestselling author Susan Wiggs   “Full of emotion and just plain fun, this novel is delightful.”—Romance Reviews Today “In this touching summer read, forgiveness benefits both the person bestowing it and the recipient.”—Kirkus Reviews

The Weird Sisters (Amy Einhorn Books/G.P. Putnam's Sons, Penguin Publishing Group, Books on Tape, 2011)
The beloved New York Times bestseller from acclaimed author Eleanor Brown about three sisters who love each other, but just don't happen to like each other very much. Three sisters have returned to their childhood home, reuniting the eccentric Andreas family. Here, books are a passion (there is no problem a library card can't solve) and TV is something other people watch. Their father—a professor of Shakespeare who speaks almost exclusively in verse—named them after the Bard's heroines. It's a lot to live up to. The sisters each have a hard time communicating with their parents and their lovers, but especially with one another. What can the shy homebody eldest sister, the fast-living middle child, and the bohemian youngest sibling have in common? Only that none has found life to be what was expected; and now, faced with their parents' frailty and their own personal disappointments, not even a book can solve what ails them...

After she's gone (Northwest, 3,, 2016)
"Cassie Kramer and her younger sister, Allie, learned the hazards of fame long ago. Together, they'd survived the horror of a crazed fan who nearly killed their mother, former Hollywood actress Jenna Hughes. Still, Cassie moved to L.A., urging Allie to follow. As a team, they'd take the town by storm. But Allie, finally free of small-town Oregon, and just that little bit more beautiful, also proved to be more talented--and driven. Where Cassie got bit parts, Allie rose to stardom. But now her body double has been shot on the set of her latest movie--and Allie is missing ..."--

Children of blood and bone (Legacy of Orisha, 1,, 2018)
Seventeen-year-old Zelie, her older brother Tzain, and rogue princess Amari fight to restore magic to the land and activate a new generation of magi, but they are ruthlessly pursued by the crown prince, who believes the return of magic will mean the end of the monarchy.

Long bright river (Riverhead Books, Penguin Publishing Group, Books on Tape, 2020)
"A suspense novel that also looks at the anatomy of a Philadelphia family rocked by the opioid crisis and the relationship between two sisters--one, suffering from addiction, who has suddenly gone missing amid a series of mysterious murders; the other a police officer who patrols the neighborhood from which she disappeared: a story about the formidable ties between place, family, and fate" --

Anything is possible (Amgash, Book 2,, 2017)
Here are two sisters: One trades self-respect for a wealthy husband while the other finds in the pages of a book a kindred spirit who changes her life. The janitor at the local school has his faith tested in an encounter with an isolated man he has come to help; a grown daughter longs for mother love even as she comes to accept her mother's happiness in a foreign country; and the adult Lucy Barton (the heroine of the author's 2016 novel My name is Lucy Barton) returns to visit her siblings after seventeen years of absence.
The sign --, Windmills --, Cracked --, The hit-thumb theory --, Mississippi Mary --, Sister --, Dottie's Bed & Breakfast --, Snow-blind --, Gift.

What we keep: a novel (Random House Publishing Group, Random House, Blackstone Publishing, 1998)
“BERG KNOWS THE HEARTS OF HER CHARACTERS INTIMATELY, showing them with compassion, humor, and an illuminating generosity.” –The Seattle Times “BEAUTIFULLY WRITTEN . . . [Ginny Young] crosses the country for a reluctant reunion with the mother she has not seen in 35 years. During the long hours of her flight, she returns in memory to the summer when she turned 12 and her family turned inside out. . . . What We Keep is about ties that are buried but not broken, wounds that are dressed but never heal, and love that changes form but somehow survives.” –USA Today “COMPELLING . . . Reading [this] book is like having an intimate conversation with a friend who is baring her soul.” –Charleston Post and Courier “TOUCHING . . . WHAT WE KEEP IS SOMETHING OF VALUE.” –San Antonio Express-News BONUS: This edition contains an excerpt from Elizabeth Berg's Once Upon a Time, There Was You.

First Comes Love (Thorndike Press large print basic, ,, 2016)
#1 NEW YORK TIMES BESTSELLER • A pair of sisters find themselves at a crossroads in this dazzling new novel from the author of Something Borrowed, Where We Belong, and The One & Only. First Comes Love is a story about family, friendship, and the courage to follow your own heart—wherever that may lead. Growing up, Josie and Meredith Garland shared a loving, if sometimes contentious, relationship. Josie was impulsive, spirited, and outgoing, Meredith hardworking, thoughtful, and reserved. When tragedy strikes, their delicate bond splinters. Fifteen years later, Josie and Meredith are in their late thirties, following very different paths. Josie, a first grade teacher, is single—and this close to swearing off dating for good. What she wants more than the right guy, however, is to become a mother—a feeling that is heightened when her ex-boyfriend’s daughter is assigned to her class. Determined to have the future she’s always wanted, Josie decides to take matters into her own hands. On the outside, Meredith is the model daughter with the perfect life. A successful attorney, she’s married to a wonderful man, and together they’re raising a beautiful four-year-old daughter. Yet lately Meredith feels dissatisfied and restless, secretly wondering if she chose the life that was expected of her rather than the one she truly desired. As the anniversary of their tragedy looms, and painful secrets from the past begin to surface, Josie and Meredith must not only confront the issues that divide them but also come to terms with their own choices. In their journey toward understanding and forgiveness, both sisters discover that they need each other more than they knew—and that in the search for true happiness, love always comes first. Praise for First Comes Love “An engaging story of sisterly love . . . Illuminating and engrossing.”—People   “[Emily] Giffin delivers another emotionally honest work. . . . First Comes Love is a heart-stirring novel about the many layers of sibling rivalry.”—Associated Press   “First Comes Love brings [Giffin] back with a vengeance. Tales of sisters have been at the core of other great novels, but Giffin turns that relationship upside down and makes her view a fascinating one.”—Huffington Post “Moving and complex, [First Comes Love] proves [that Emily Giffin is] still at the top of her game.”—Booklist “Giffin juggles Josie’s quest for motherhood and Meredith’s internal conflicts deftly. . . . Giffin paints a realistic portrait of the troubled and complex relationship between a pair of sisters.”—Kirkus Reviews “This is Giffin at her finest—a fantastic, memorable story.”—Publishers Weekly    “First Comes Love is an un-put-down-able, smart, and thoughtful novel that will make you think about the nature of family and how our past informs our present.”—PopSugar “Giffin’s talent is pretty much unparalleled when it comes to the modern woman’s story about life, love and family.”—Redbook “[A] well-written family drama.”—Real Simple “Fans will be entertained by the author’s humor and satisfied by her storytelling”—Atlanta Journal-Constitution

Pride and prejudice (Blackstone Audio, Inc., Duke Classics, Spotify Audiobooks, 2008)
"When Elizabeth Bennet first meets eligible bachelor Fitzwilliam Darcy, she thinks him arrogant and conceited; he is indifferent to her good looks and lively mind. When she later discovers that Darcy has involved himself in the troubled relationship between his friend Bingley and her beloved sister Jane, she is determined to dislike him more than ever. In the sparkling comedy of manners that follows, Jane Austen shows the folly of judging by first impressions and superbly evokes the friendships, gossip and snobberies of provincial middle-class life." --OCLC

Dark Places (Crown, Books on Tape, Three Rivers Press, 2009)
After witnessing the murder of her mother and sisters, seven-year-old Libby Day testifies against her brother Ben, but twenty-five years later she tries to profit from her tragic history and admit that her story might not have been accurate.

Mrs. Everything: a novel (Simon & Schuster Audio, Atria Books, Center Point Large Print, 2019)
"A smart, thoughtful, and timely exploration of two sisters' lives from the 1950s to the present as they struggle to find their places--and be true to themselves--in a rapidly evolving world. Mrs. Everything is an ambitious, richly textured journey through history--and herstory--as these two sisters navigate a changing America over the course of their lives"--

Little Women (Little Women, ,, 2009)
"After her first literary success with Hospital Sketches, a book based on her experiences in the Civil War, and her secret career as the author of 'rubbishy novels' to contribute to the family income, Louisa May Alcott was asked by her publisher to write a 'girl's book.' Alcott grudgingly complied with this semiautobiographical novel of four very different sisters and their beloved Marmee struggling to keep a home with their father away at war--and produced a popular and enduring classic that has captivated generations of readers."--back cover

The magician's elephant (Candlewick Press, 2009)
When ten-year-old orphan Peter Augustus Duchene encounters a fortune teller in the marketplace one day and she tells him that his sister, who is presumed dead, is in fact alive, he embarks on a remarkable series of adventures as he desperately tries to find her.

Atonement: a novel (Anchor Books, Knopf Doubleday Publishing Group, 2007)
NATIONAL BESTSELLER • A symphonic novel of love and war, childhood and class, guilt and forgiveness that provides all the satisfaction of a brilliant narrative and the provocation we have come to expect from the acclaimed Booker Prize–winning, internationally bestselling author. On a hot summer day in 1935, thirteen-year-old Briony Tallis witnesses a moment’s flirtation between her older sister, Cecilia, and Robbie Turner, the son of a servant and Cecilia’s childhood friend. But Briony’s incomplete grasp of adult motives—together with her precocious literary gifts—brings about a crime that will change all their lives. As it follows that crime’s repercussions through the chaos and carnage of World War II and into the close of the twentieth century, Atonement engages the reader on every conceivable level, with an ease and authority that mark it as a genuine masterpiece. Don’t miss Ian McEwan’s new novel, Lessons.

The War that Saved my Life (Books on Tape, Penguin Young Readers Group, 2015)
A young disabled girl and her brother are evacuated from London to the English countryside during World War II, where they find life to be much sweeter away from their abusive mother.

The Color Purple (The Color Purple, ,, 1992)
The Pulitzer Prize– and National Book Award–winning novel is now a new, boldly reimagined film from producers Oprah Winfrey and Steven Spielberg, starring Taraji P. Henson, Danielle Brooks, and Fantasia Barrino. A PBS Great American Read Top 100 Pick Celie has grown up poor in rural Georgia, despised by the society around her and abused by her own family. She strives to protect her sister, Nettie, from a similar fate, and while Nettie escapes to a new life as a missionary in Africa, Celie is left behind without her best friend and confidante, married off to an older suitor, and sentenced to a life alone with a harsh and brutal husband. In an attempt to transcend a life that often seems too much to bear, Celie begins writing letters directly to God. The letters, spanning 20 years, record a journey of self-discovery and empowerment guided by the light of a few strong women. She meets Shug Avery, her husband’s mistress and a jazz singer with a zest for life, and her stepson’s wife, Sofia, who challenges her to fight for independence. And though the many letters from Celie’s sister are hidden by her husband, Nettie’s unwavering support will prove to be the most breathtaking of all. The Color Purple has sold more than five million copies, inspired an Academy Award-nominated film starring Oprah Winfrey and directed by Steven Spielberg, and been adapted into a Tony-winning Broadway musical. Lauded as a literary masterpiece, this is the groundbreaking novel that placed Walker “in the company of Faulkner” (The Nation), and remains a wrenching—yet intensely uplifting—experience for new generations of readers. This ebook features a new introduction written by the author on the 25th anniversary of publication, and an illustrated biography of Alice Walker including rare photos from the author’s personal collection. The Color Purple is the 1st book in the Color Purple Collection, which also includes The Temple of My Familiar and Possessing the Secret of Joy.

Malibu rising: a novel (Random House Large Print, Random House Publishing Group, Books on Tape, 2021)
Four famous siblings throw an epic end-of-summer party that goes dangerously out of control as secrets and loves that shaped this family's generations come to light, changing their lives forever.